Effect of exercise on symptoms of premenstrual syndrome in low and middle-income countries: a protocol for systematic review and meta-analysis - Rakibul M Islam; Pratik Pokharel; Juwel Rana; Jude Moutchia; Shreeshti Uchai; Aldiona Kerri; Patricia Lorena Luna Gutiérrez (BMJ Open, 2020)
Introduction Premenstrual syndrome (PMS) has the potential to affect the quality of life adversely. Published guidelines recommend the use of exercise as part of the first-line management interventions for PMS. However, the published evidence related to the effectiveness of physical activity and PMS is inconclusive. This review will assess the effectiveness of exercise-based interventions in reducing PMS in women screened or diagnosed with PMS in low and middle-income countries, where the prevalence of PMS is high.Methods and analysis Electronic databases will be researched, including Embase, Cochrane Central Register of Controlled Trials, MEDLINE, PsycINFO, Web of Science, ClinicalTrials.gov and Google Scholar. All the studies published until March 2020 will be included. A standardised data extraction form will be used adapted from the Cochrane Handbook of Systematic Reviews of Interventions. Included articles will be assessed using the risk of bias tools based on study design. Data will be analysed using Review Manager V.5.3. The inverse-variance random-effects method will be used to report the standardised mean difference. A meta-analysis will be used only if studies are sufficiently homogenous. A narrative synthesis will be undertaken when studies are heterogeneous. Methodological heterogeneity between studies will be evaluated by considering the study types. Statistical heterogeneity will be tested using the I2 test. Subgroup analyses may be performed only for the primary outcome in case of sufficient studies. Sensitivity analysis will be conducted to assess the impact of intervention excluding studies without randomisation and studies with a high risk of bias. Funnel plots will be used to assess the potential reporting bias and small-study effects only when there are more than 10 studies included in the meta-analysis.Ethics and dissemination This study does not require ethical approval, as the review is entirely based on published studies. The results will be published and/or will be presented at a pertinent conference.PROSPERO registration number CRD42020163377.